Drug Information Services in Nepal: An Overview, Present Scenario and Future Perspective - Pandey, Trilochan; Maharjan, Pawan; Dhakal, Subodh; Dongol, Prity; Lama, Puja; Shrestha, Sharmila; Dangal, Ganesh (Journal of Karnali Academy of Health Sciences, 2022)
Drug Information Centre (DIC) provides services regarding several aspects of drugs’ information, to healthcare professionals and consumers, that are impartial, updated, well-referenced, and critically evaluated. These information required ranges from therapeutic information for the treatment of patient, comparision of efficacy, potency and costs, market availability to even recent advances in drugs.